Developing Global Competency-Challenges and Opportunities - Subramaniam, D.; Shyama Sundar, K. (Indian Journal of Marketing, 2011)
Globalization has necessitated the need to develop "Global Competencies" among the nations and the enterprises. Also, there is a threat for the domestic firm by way of entry of a global firm into the domestic market which compels that it should develop competency to thwart the onslaught of the global firm and still survive in the business. Michael E. Porter's formula of linking the "productivity" and "competitiveness" is used in this article to interpret the impact of various values that go into the making of the formula to establish Global productivity of factors. Also, the article identifies certain factors which are very critical for the Global competencies' development and discusses the current trends on those lines and is trying to make a pattern out of it for a meaningful insight.